Neohesperidin Protects Angiotensin II-Induced Hypertension and Vascular Remodeling - Zhang, Jingsi; Hui, Yuanshu; Liu, Fengyi; Yang, Qian; Lu, Yi; Chang, Yeting; Liu, Qinlong; Ding, Yanchun (Frontiers in Pharmacology, 2022)
Vascular remodeling due to hypertension is one of the major health challenges facing countries around the world. Neohesperidin, a flavonoid glycoside found in citrus fruits, is an antioxidant. Neohesperidin has been studied for a variety of diseases in addition to hypertension. In this study, angiotensin II was used to induce hypertension in mice (490 ng/kg/min, 14 days). We used H&E, Masson, immunofluorescence, dihydroethidine and qPCR to evaluate the effect of Nehesperidin (50mg/kg/day, 16 days) on pathological hypertension in mice. Estimating the effect of Nehesperidin on human umbilical vein endothelial cells and vascular smooth muscle cells stimulated by angiotensin II. We found that neohesperidin inhibited angiotensin II-induced hypertension in mice. Neohesperidin reduced angiotensin II-induced vascular hypertrophy, fibrosis, inflammation and oxidative stress in vivo. Neohesperidin inhibited angiotensin II-induced ROS and DNA damage in human umbilical vein endothelial cells. Neohesperidin inhibited angiotensin II-induced migration of vascular smooth muscle cells. The results showed that Nehesperidin acts as an antioxidant and could significantly inhibit angiotensin II induced hypertension and vascular remodeling in vitro and in vivo.